Arabic Language Learning Model Based on The Merdeka Curriculum - Anwar Ridwan Nulloh; Fikri Bahruddin Ar Romli; Moch Cecep Abdul Azis; Muhammad Andhika Silmi (UIN Sunan Gunung Djati Bandung, 2025)
The learning model and curriculum are among the most crucial components of the educational process, significantly influencing the quality of learning outcomes. These aspects shape how teachers plan instruction, implement strategies during lessons, and conduct assessments throughout and after the learning process. This study aims to examine the planning, implementation, and evaluation of Arabic language learning based on the Merdeka (Independent) Curriculum at MAN 1 Bandung City. The research method employed is qualitative, using data collection techniques such as observation, interviews, and documentation. The findings reveal that the planning, implementation, and evaluation of Arabic instruction are aligned with KMA No. 347 of 2022, KMA No. 450 of 2024, and the Decree of the Director General of Islamic Education No. 3302 regarding the achievement standards of Islamic Education and Arabic Language. Furthermore, the model is adapted to the specific context and characteristics of the school. The Arabic language learning model based on the Merdeka Curriculum at MAN 1 Bandung integrates three key aspects: knowledge content, technology, and communication. This integration supports a more holistic and student-centered learning approach, contributing to the development of both linguistic competence and 21st-century skills.